Pengaruh Perencanaan Pajak, Multinationality dan Intangible Assets Terhadap Keputusan Transfer Pricing - Yuliani Fadillah Azzahra; Dirvi Surya Abbas; Daniel Rahandri (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The purpose of this study is to determine the effect of tax planning size, multinationality and intangible assets with foreign ownership as a moderation variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the period 2017-2021. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique uses purposive sampling technique. Based on the established criteria, 8 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results of the study partially show that tax planning has a positive effect on Transfer Pricing decisions. Multinatinality negatively affects Transfer Pricing decisions. Intangible assets have no influence on Transfer Pricing decisions.